Family doctors to connect global concerns due to climate change with local actions: State‐of‐the art and some proposals. Issue 2 (9th June 2021) - Lauriola, Paolo; Serafini, Alice; Santamaria, Mariagrazia; Guicciardi, Stefano; Kurotschka, Peter K.; Leonardi, Giovanni S.; Zeka, Ariana; Segredo, Evelyn; Bassi, Maria C.; Gokdemir, Ozden; de Tommasi, Francesco; Vinci, Emanuele; et al.
Abstract: Climate change (CC) is the most challenging environmental health (EH) concern. Air pollution is closely linked to CC. However, many CC‐health‐related conditions (i.e., allergic diseases, asthma, hypertension, fluid and electrolyte disorders, child and adult obesity, type 2 diabetes, vector‐borne diseases) are not usually counted, either because they do not cause death or require hospital admission/emergency triage. They are the vast majority of health care seeking generally treated by family doctors (FDs) and family pediatricians (FPs). FDs/FPs are often not aware of CC‐health‐impacts. Their potential role in tackling such a global challenge through their local influence on individual and collective attitudes and policies is not considered. Proper FD training could fill these gaps, raise awareness of their role, and implement EH FDs/FPs‐based surveillance networks to collect, analyze, interpret, and report EH data to inform EH‐related Policy. FDs and FPs, organized in sentinel physicians' networks, could play a key role in advising policymakers at the local and regional level in designing interventions adapted to climate‐related issues. Such experiences are rare worldwide and not well known. We will describe and discuss them in detail to share successful local examples. Key Points: Climate change (CC) is presently the most challenging environmental health (EH) concern. Air pollution which is closely linked to CC, is responsible for 7 million deaths per year. These figures, however, underestimate the overall health impacts of CC and environmental threats. Many conditions are not usually counted, either because they do not cause death, or require hospital admission/emergency triage. They are generally treated by family doctors (FDs). Hence they should be counted either to assess citizens day‐to‐day quality life or to allocate resources in healthcare services properly. Nonetheless, FDs are often not aware of CC and EH effects impacts. As such their potential role to tackle such a global challenge through their local influence on individual and collective attitudes and policies has not been fully considered so far.